Reliability and relevance of fair values: private equity investments and investee fundamentals - Ferreira, Petrus H.; Kräussl, Roman; Landsman, Wayne R.; Borysoff, Maria Nykyforovych; Pope, Peter F. (Review of Accounting Studies, 2019)
We directly test the reliability and relevance of investee fair values reported by listed private equity funds (LPEs). In our setting, disaggregated fair value measurements are observable for funds’ investees; and investee accounting fundamentals are also publicly disclosed. We find that LPE fair value measurements reflect equity book value and net income in a manner consistent with stock market pricing of listed companies. However, LPE fair value measurements appear to distinguish between Level 1 and Level 3 inputs – they reflect investee net income to a lesser extent for Level 3 inputs. Further evidence based on the stock market pricing of LPE funds indicates that the discretion exercised by LPE fund managers when determining investee valuations is perceived as reliable.